Public Sphere Creates Independence for Coastal Women in Encouraging the Household Economy of Small-Scale Fishermen in Karangsong Village, Indramayu Regency - Anisti, Anisti; Sarwoprasodjo, Sarwititi; Sumardjo, Sumardjo; Amanah, Siti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Marine climate change has resulted in a decline in the economic level of fishermen, especially small-scale fishermen who depend on marine resources to meet their daily needs. In addition, the poverty experienced by fishermen reflects economic vulnerability due to low and unstable incomes, which are caused by fluctuating market prices, a lack of alternative livelihoods, insufficient cooperation and support networks, and the prevalence of illegal fishing practices. By carrying out dialogue in the public sphere effectively, a supportive environment can be created for small-scale fishermen to optimize the potential of the public sphere in improving the family economy through increasing human resource skills. In this framework, coastal women play a vital role in the economic activities of small-scale fishermen's households through alternative economies. This research aims to investigate the role of dialogue in the public sphere to improve the economy of small-scale fishermen in coastal areas and explore the role of women in efforts to improve the family economy. This research uses a qualitative descriptive method with a case study approach. The research results show that dialogue in the public sphere has been recognized as a means of building better understanding between various parties in society, as well as the importance of involving women in family economic decision-making. This research provides implications from the concept of dialogue theory in the public sphere, reflecting the concept of community participation and creating mutual agreement through open communication and the exchange of ideas in formulating solutions to improve the family economy.